2010
DOI: 10.4028/www.scientific.net/msf.638-642.3105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bar-Like Carbides in HR3C Boiler Steel

Abstract: After the heat treatment at 1200 oC 30 minutes followed by water cooling and 700 oC 4 hours for HR3C (S31042) boiler steel, the bar-like carbides precipitate in grain boundaries and within grains. It was found that the bar-like carbides nucleate in the grain boundaries and grew into grains in a parallel manner. With the help of TEM, the carbides were characterized to be M23C6, with a length of about 6μm and width of 0.6-0.8μm. Through observing crept specimens after testing at 700 oC, it was found that fine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sourmail found that M 23 C 6 precipitates on the grain boundaries in 22Cr-25Ni-Mo-Nb-N after aging [10]. And Cheng also finds M 23 C 6 precipitates on the grain boundaries in 25Cr-20Ni-Nb-N after aging [11]. SEM/EDS were used to identify the precipitates on the grain boundaries in both steels.…”
Section: Precipitates On the Grain Boundarymentioning
confidence: 98%
“…Sourmail found that M 23 C 6 precipitates on the grain boundaries in 22Cr-25Ni-Mo-Nb-N after aging [10]. And Cheng also finds M 23 C 6 precipitates on the grain boundaries in 25Cr-20Ni-Nb-N after aging [11]. SEM/EDS were used to identify the precipitates on the grain boundaries in both steels.…”
Section: Precipitates On the Grain Boundarymentioning
confidence: 98%
“…Exuding of precipitates occurs especially during the first 2000 hours of operational load. After that the microstructure and mechanical properties are almost constant [6,7]. Because the precipitates doesn't exclude until the operational load to determine the grain growth kinetics in HAZ of welds of unloaded materials it is considered, that ideal grain growth is controlled only by diffusion (exponent m=2).…”
Section: Obtaining Of Input Data and Determination Of Grain Growth Ki...mentioning
confidence: 99%